An essential Trypanosoma brucei protein kinase: a functional analysis of regulation and the identification of inhibitors - Parsons, Marilyn; Parsons, Ben; Dean, Marissa; DeRocher, Amy E.; Islam, Zeba; Maly, Dustin J.; Jensen, Bryan C. (Frontiers in Parasitology, 2023)
Introduction The protein serine/threonine kinase AEK1 is essential in the pathogenic stage of Trypanosoma brucei, the causative agent of African trypanosomiasis. AEK1 is a member of the AGC protein kinase family, although it is not closely related to a specific human AGC kinase. Our previous chemical genetic studies showed that targeted inhibition of AEK1 in parasites expressing analog-sensitive AEK1 blocked parasite growth and enhanced survival of infected mice. Methods To further validate AEK1 as a drug target, we used the chemical genetic system to determine the effect of a 24 hour loss of AEK1 activity on cell viability at the clonal level. A panel of 429 protein kinase inhibitors were screened against the wild-type protein for binding, using time-resolved fluorescence energy transfer (TR-FRET). The role of phosphorylation sites and motifs was probed by determining whether expression of proteins harboring mutations in these sequences could rescue AEK1 conditional knockout parasites. To determine the effect that mutations in the phosphosites have on the kinase activity of cellular AEK1 we compared the in vitro kinase activity of mutant and wild-type proteins immunoprecipitated from parasite lysates using the exogenous substrate MBP. Finally, the tagged AEK1 protein was localized by deconvolution microscopy. Results After a 24 hour exposure to an AEK1 inhibitory analog in the chemical genetic system, less than five percent of the remaining live cells can clonally expand, further validating AEK1 as a drug target. In the AEK1 inhibitor screening assay, we identified 17 hit compounds. Complementation studies showed that of the two known phosphorylation sites in the activation loop; mutation of one abolished function while mutation of the other had no discernable effect. Mutation of the other two AEK1 phosphosites gave intermediate phenotypes. Mutations in either the hydrophobic motif at the C-terminus of the protein or in the region of AEK1 predicted to bind the hydrophobic motif were also required for function. All parasites with defective AEK1 showed reduced proliferation and defects in cytokinesis, although the tested mutations differed in terms of the extent of cell death. Kinase activity of immunoprecipitated AEK1 phosphosite mutants largely paralleled the effects seen in complementation studies, although the mutation of the phosphosite adjacent to the hydrophobic motif had a greater impact on activity than predicted by the complementation studies. AEK1 was localized to cytoplasmic puncta distinct from glycosomes and acidocalcisomes. Discussion The rapid loss of viability of cells inhibited for AEK1 supports the idea that a short course of treatment that target AEK1 may be sufficient for treatment of people or animals infected with T. brucei. Key regulatory elements between AEK1 and its closest mammalian homolog appear to be largely conserved despite the vast evolutionary distance between mammals and T. brucei. The presence of AEK1 in cytoplasmic puncta raises the possibility that its localization may also play a role in functional activity.